Denarna kazen - Filipčič, Katja (Pravnik, 2016)
The financial penalty is well received in Europe, since it makes up more than half of all imposed penalties in most countries. It has gone through many changes since its first introduction. The most important one being the introduction of the day-fine, which allows social fairness at imposition. One of the main issues of the financial penalty is its replacement with a prison sentence in case of non-payment, since the offender is given a sentence which does not reflect the gravity of the offences. Countries seek to achieve a greater share in the exceution of financial penalties in different ways, such as introducing community service as a substitute to prison for fine defaulters. In Slovenia the role of the financial penalty is different to most other European countries; after 1990 its share began to drop severely and constituted less than 4% in 2014. Statistics show that some courts impose it far more often than others, which undermines the principle of equal punishment.
Keywords: denarne kazni; kazenske sankcije; kazniva dejanja